Acceleration of the short high-current compensated ion bunches in the peaked fence magnetic field with additional space charge compensation by thermal electrons: 2d3v PIC simulation - Manuilenko, O.V. (Вопросы атомной науки и техники, 2013)
The particle in cell simulation results, within the limits of the complete set of the Maxwell-Vlasov equations, of the short high-current compensated tubular ion bunches transportation and acceleration in the peaked fence magnetic field are presented. The ion bunch current, at injection in the cusp, is compensated by electrons. It is shown that additional compensation of the accelerated ion bunch space charge by thermal electrons leads to reduction of its energy dispersion and divergence on an exit from the cusp. It is shown also that overcompensation of the ion bunch space charge by thermal electrons leads not only to increase of energy spread and divergence of an ion bunch on an exit from the cusp, but also to deceleration of an ion bunch. Приведены результаты моделирования методом макрочастиц в рамках полной системы уравнений Власова- Максвелла, транспортировки и ускорения коротких сильноточных трубчатых ионных сгустков в магнитном поле остроугольной геометрии. Ток ионного сгустка при инжекции в касп скомпенсирован электронами. Показано, что дополнительная компенсация объемного заряда ионного сгустка тепловыми электронами приводит к уменьшению его энергетического разброса и расходимости на выходе из каспа. Показано также, что перекомпенсация объемного заряда ионного сгустка тепловыми электронами ведет не только к увеличению разброса по энергии и расходимости ионного пучка на выходе из каспа, но и к замедлению ионного сгустка. Наведено результати моделювання методом макрочасток у рамках повної системи рівнянь Власова-Максвелла, транспортування та прискорення коротких сильнострумових трубчастих іонних згустків у магнітному полі гострокутної геометрії. Струм іонного згустка при інжекції у касп, скомпенсовано електронами. Показано, що додаткова компенсація об'ємного заряду іонного згустка тепловими електронами приводить до зменшення його енергетичного розкиду і розбіжності на виході з каспа. Показано також, що перекомпенсація об'ємного заряду іонного згустка тепловими електронами веде не тільки до збільшення розкиду по енергії і розбіжності іонного пучка на виході з каспа, але і до уповільнення іонного згустка.